Proceedings of the 2008 ACM Conference on Computer Supported Cooperative Work 2008
DOI: 10.1145/1460563.1460596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the deployment of a mobile technology in a hospital ward

Abstract: Since health care teams are often distributed across time and location, information sharing is crucial for effective patient care. Studying the use of a mobile information technology in a local hospital ward at two months and eleven months after its deployment identifies both shortand long-term phenomena and reveals a mismatch between the intentions behind the deployed mobile technology and the nurses' current work practices. We contrast the new mobile technology with the paper artifacts that were previously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…These systems and applications have the potential to improve patient care and the efficiency with which it is delivered. In practice, the majority of research in pervasive computing technologies for healthcare has been focused on hospital work (e.g., [3,4,7,10,11,15,20,23,59,61,62,66]. However, hospitals are just one of many locations where novel technological interventions for healthcare are needed.…”
Section: Related Workmentioning
confidence: 99%
“…These systems and applications have the potential to improve patient care and the efficiency with which it is delivered. In practice, the majority of research in pervasive computing technologies for healthcare has been focused on hospital work (e.g., [3,4,7,10,11,15,20,23,59,61,62,66]. However, hospitals are just one of many locations where novel technological interventions for healthcare are needed.…”
Section: Related Workmentioning
confidence: 99%
“…Notably, interaction with paper documents has been scrutinized heavily in context of affordances. Prior studies (Bardram and Bossen 2005b;Chen 2010;Tang and Carpendale 2008) but this paper as well show that paper documentation remains to play an important central role as it is persistently and pervasively used during medical work in hospitals. This intensive use of paper documentation is independent from the degree to which EHR are integrated as paper simply makes clinicians more efficient in parts of their work (Saleem et al 2009).…”
Section: Collaborative Affordancesmentioning
confidence: 59%
“…The portability affordance of the HyPR is much closer to that of a paper-based medical record, especially if compared to other approaches that attempt to include mobility use for the EHR (e.g., Computers on Wheels (COW) (Tang and Carpendale 2008)). …”
Section: S H a R E D Overviewmentioning
confidence: 99%
“…In contrast, the process of updating information via digital devices such as PDAs or Tablet PCs is slower (Silva et al 2006). Studies also found that nurses relied heavily on their paper personal artefacts when delivering patient care, even when alternative mobile information technology was available, e.g., a computer-onwheels with bedside information access (Tang & Carpendale 2008). In fact, many nurses in our study ward regarded these paper personal artefacts as indispensible to their nursing work and non-replaceable.…”
Section: Introductionmentioning
confidence: 80%